2015
DOI: 10.1167/iovs.14-15687
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Light-Evoked Responses of the Posterior Segment in a Mouse Model of Diabetic Retinopathy

Abstract: Apparent diffusion coefficient MRI is a sensitive method for evaluating choroid thickness and its light-evoked expansion together with phototransduction-dependent changes in the SRS layer in mice in vivo. Because ADC MRI exploits an endogenous contrast mechanism, its translational potential is promising; it can also be performed in concert with manganese-enhanced MRI (MEMRI). Our data support a link between diabetes-related oxidative stress and rod, but not choroidal, pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
132
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(149 citation statements)
references
References 49 publications
(96 reference statements)
17
132
0
Order By: Relevance
“…Thus, at the present resolution, we previously demonstrated that MRI can distinguish rod inner segment from outer segment based on the light-evoked expansion of the subretinal space in mice and rats, as well as, for example, (1) inner from outer retina manganese uptake as a function of light, (2) DIL-induced suppression of only inner retinal manganese uptake, and (3) the outer nuclear layer-only tetrameric visual arrestin 1 and its reduction via light-evoked translocation. 28,29,50,51 These examples strongly support our claim that the resolution of MRI is sufficient for extracting meaningful layer-specific functional data in vivo. In all cases, animals were humanely euthanized as detailed in our IACUCapproved protocol.…”
Section: Mri Proceduressupporting
confidence: 68%
See 4 more Smart Citations
“…Thus, at the present resolution, we previously demonstrated that MRI can distinguish rod inner segment from outer segment based on the light-evoked expansion of the subretinal space in mice and rats, as well as, for example, (1) inner from outer retina manganese uptake as a function of light, (2) DIL-induced suppression of only inner retinal manganese uptake, and (3) the outer nuclear layer-only tetrameric visual arrestin 1 and its reduction via light-evoked translocation. 28,29,50,51 These examples strongly support our claim that the resolution of MRI is sufficient for extracting meaningful layer-specific functional data in vivo. In all cases, animals were humanely euthanized as detailed in our IACUCapproved protocol.…”
Section: Mri Proceduressupporting
confidence: 68%
“…At 2 months of age, 20-g male C57Bl/6 mice (Jackson Laboratories, Bar Harbor, ME, USA) were randomly divided into the following groups and were studied after 2 months of diabetes (or age-matched): (1) a non-diabetic control group (wild type [wt]); (2) a diabetic group (D); (3) a Dþ11-cisretinaldehyde group (Dþ11-cis); and (4) a Dþ9-cis-retinaldehyde (Dþ9-cis); note that the ADC MRI data for groups i and ii were previously published (29). Retinaldehydes were delivered systemically.…”
Section: Experimental Groupsmentioning
confidence: 99%
See 3 more Smart Citations